Investigating The Risk of Glove Punctures in Aseptic Processing Barrier Technology Systems: A Case Study - Kemlall Ramsaroop Ramdass; Phumzile Mabaso; Bongumenzi Mncwango (International ABEC, 2022)
Aseptic processing is a method of production that is free of microbiological, pyrogen, and particulates and thus it is perceived as one of the most complex manufacturing processes in the pharmaceutical industry. Due to the significant risks associated with aseptic processing a quality risk management (QRM) program is necessary to protect the patient from injury. This study aims to investigate the process followed when glove punctures are detected on glove sleeves of barrier technology systems in a sterile manufacturing facility. Further, this paper utilizes an example of a risk assessment method to illustrate how a risk assessment can be useful in aseptic processing operations. The specific activity being investigated involves glove punctures during aseptic filling operations. The risk assessment approach adopted is in the form of a Fishbone diagram. The findings of the study will provide insights that will aid developing organizations to overcome challenges associated with aseptic processing